Augmented Reality Flipbook as a Guide to Determining the Main Idea of Paragraphs in Indonesian Language Learning - Ekasafitri, Melly; Sismulyasih SB, Nugraheti; Purwati, Panca Dewi (International Journal of Elementary Education, 2024)
In the learning process, students still have difficulty in understanding the material well. In its implementation, the teacher uses conventional teaching materials, less varied and not yet digital-based by actively involving students. The purpose of this study was to develop and test the effectiveness of augmented reality-based flipbooks on the main idea of paragraphs of Indonesian language learning content in grade V elementary school. The type of research is the Research & Development (R&D). The subjects of this study were teachers, 1 media expert, 1 material expert, and fifth-grade students, namely 6 initial trial students and 13 usage trial students. The data collection methods used include observation, interviews, questionnaires, and tests. Data analysis techniques used include qualitative data analysis, quantitative data analysis, normality test, N-Gain, and inferential statistical analysis (t-test). The results of the study are the feasibility test by media experts obtained a percentage of 92% (very feasible), material experts are 91.25% (very feasible), student and teacher response trials obtained a percentage of 95.31%, and 92.5% (very feasible). The results of the t-test (paired t-test) obtained differences in results between before (pretest) and after (posttest) grade V students using augmented reality-based flipbooks. N-Gain test results 0.61 (medium). It is concluded that the augmented reality-based flipbook is very feasible and effective to use in learning. This research implies that augmented reality-based flipbooks can facilitate students' understanding of learning materials so that they can improve students' cognitive abilities in determining the main idea of paragraphs in Indonesian language learning.